Influence of Different Experimental Conditions on Bond Strength of Self-Adhesive Synthetic Polymer System Hydrogels for Biological Applications - Garcia-Herrera, C; Inostroza-Inostroza, M; Martin-Trasancos, R; Martin-Trasancos, R (Elsevier B.V., 2025)
Poly(2-hydroxyethyl methacrylate) P(HEMA) is a biocompatible and hydrophilic polymer with significant potential for drug delivery and various biomedical applications. The main goal is to adapt these materials for biological applications. This work contributes to designing an adhesive polymeric system based on hydrophilic polymers using vinyl monomers via radical polymerization. The hydrogels were produced via free radical polymerization in an aqueous environment, with variations in the initial experimental conditions, including different ratios of initial monomers and the cross-linking agent. This was done to analyze the strength of the self-adhesive bond of synthetic hydrogels for potential biological applications. The functional groups of the hydrophilic monomers were employed to explore possible chemical modifications in the environment (adhesive properties) through physical interactions, such as hydrogen bonding and van der Waals forces between the polymer chains. This could allow for the incorporation of active biomolecules, potentially enhancing physical bonding through hydrogen bridges between polymer chains. These hydrogels have been characterized by their thermal stability, swelling behavior, and adhesive strength in a wet medium. The hydrogel demonstrated the highest adhesive strength at a 2:1 feed monomer ratio with 0.5 mol-% of N N-methylene bisacrylamide (MBA) in a damp medium, indicating significantly improved adhesive properties compared to other MBA percentages. Moreover, a reduction in hydrogel swelling correlated with enhanced adhesion, showing more than a 6.5-fold increase in adhesion compared to the 1:1 feed monomer ratio at 0.5 mol-% MBA and an 18-fold increase compared to the 1:1 feed monomer ratio at 0.1 mol-% MBA. © 2024